Revisiting dithiadiaza macrocyclic chelators for copper-64 PET imaging - Shuvaev, Sergey (Dalton Trans, 2020)
Synthesis and characterisation of a dithiadiaza chelator NSNS2A, as well as copper complexes thereof are reported in this paper. Molecular structures of copper (I/II) complexes were calculated using density-functional theory (DFT) further validated by both NMR and EPR spectroscopy. DFT calculations revealed a switch in the orientation of tetragonal distortion upon protonation, which might be responsible for poor stability of Cu((II))NSNS2A complex in aqueous media, whilst the same switch in tetragonal distortion was experimentally observed by changing the solvent. The chelator was radiolabeled with (64)Cu and evaluated using PET/MRI in rats. Despite a favorable redox potential to stabilize the cuprous state in vivo, (64)Cu((II))NSNS2A complex showed suboptimal stability compared to its tetraazamacrocyclic analogue, (64)Cu(TE2A), with a significant (64)Cu uptake in the liver.